Cerebral blood flow and blood rheology in hypertensive patients during rilmenidine treatment - L. I. Markova; E. V. Evdokimova; A. E. Radzevich (Российский кардиологический журнал, 2004)
Cerebral blood flow, blood rheology and viscosity during 6-month rilmenidin therapy (Albarel, Egis) were measured in 50 patients with arterial hypertension (JNC VII, 2003). Rilmenidin was administered once a day, in the dose of 1-2 mg/d. Total cerebral blood flow and venous drainage, assessed with Doppler ultrasonography, were initially reduced. By the end of the study, they increased significantly, by 16 % and 12,5 %, respectively. Rheology and viscosity parameters improved substantially, too.